Implementasi Kurikulum Kulliyatul Mu’allimat al Islamiyah (KMI) dalam Pembinaan Akhlak Mulia Santriwati di Pondok Pesantren Annajiyah Lubuklinggau - Karti, Aisyah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
The purpose of this study to understand Implementation of the Kulliyatul Mu'allimat Al-Islamiyah (KMI) curriculum in fostering noble character for students. This study used a qualitative research approach. Data collection through observation, interviews, and documentation. Data analysis techniques, and triangulation. The results show that the implementation of the KMI curriculum, in fostering the noble character of female students at the Annajiyah Islamic Boarding School, Lubuklinggau, is influenced by several Gontor-style leadership qualifications, direction and assignment as an applicative effort to build discipline awareness and foster noble character. The KMI curriculum and discipline in the context of fostering noble character in this Islamic boarding school are applied in patterned activities, daily, weekly, semi-annual, and yearly, fostering the noble character of this boarding school through strategies and methods of implementation, but still has not reached the maximum target, still obstacles, from the factors of students, teachers, infrastructure and guardians of students.